FioStar Wave Recycle - Hairul, Ziana; Rusman, Suleha; Sabdullih, Mohd Sahfie; Kassim, Nur Zawana; Bidin, Nur Ezzatul Afiqah (2021)
FioStar Wave Recycle is an organization that is a partnership-based form of company. It means that this business establishes a type of collaboration. For five members, such as General Manager, Administration Manager, Marketing Manager, Operations Manager and Financial Manager, the relationship form under this business consists of and holds the position.